HPV vaccine acceptability in high-risk Greek men - Lea Hoefer; Savas Tsikis; George Bethimoutis; Electra Nicolaidou; Vassilios Paparizos; Christina Antoniou; Antonios Kanelleas; Leonidas Chardalias; Georgios-Emmanouil Stavropoulos; John Schneider; Angella Charnot-Katsikas (Taylor & Francis Group, 2018)
HPV is associated with malignancy in men, yet there is a lack of data on HPV knowledge, vaccine acceptability, and factors affecting vaccine acceptability in Greek men. This study aims to identify determinants of knowledge and willingness to vaccinate against HPV among high-risk Greek men. Men (n = 298) between the ages of 18 and 55 were enrolled from the STI and HIV clinics at "Andreas Syggros" Hospital in Athens, Greece from July-October 2015. Participants completed a survey on demographics, economic factors, sexual history, HPV knowledge, and vaccine acceptability. The majority of participants were younger than 40 (76.6%) and unmarried (84.6%). Our sample was 31.2% MSM (men who have sex with men), and 20.1% were HIV-positive. Most participants (>90%) were aware that HPV is highly prevalent in both men and women; however, fewer identified that HPV causes cancers in both sexes (68%) and that vaccination protects men and women (67%). Amongst participants, 76.7% were willing to vaccinate themselves against HPV, 71.4% an adolescent son, and 69.3% an adolescent daughter. HIV-positive men were more likely to be willing to vaccinate themselves (OR 2.83, p = .015), a son (OR 3.3, p = .015) or a daughter (3.01, p = .020). Higher income levels were associated with increased willingness to vaccinate oneself (OR 1.32, p = .027), a son (1.33, p = .032) or daughter (1.34, p = .027). Although there is a HPV knowledge gap, HPV vaccine acceptability is high despite lack of vaccine promotion to Greek men. Future studies should include lower-risk men to adequately inform public health efforts.